Impairment of episodic memory in genetic frontotemporal dementia: A GENFI study. Issue 1 (13th May 2021) - Poos, Jackie M.; Russell, Lucy L.; Peakman, Georgia; Bocchetta, Martina; Greaves, Caroline V.; Jiskoot, Lize C.; van der Ende, Emma L.; Seelaar, Harro; Papma, Janne M.; van den Berg, Esther; Pijnenburg, Yolande A.L.; Borroni, Barbara; et al.
Abstract: Introduction: We aimed to assess episodic memory in genetic frontotemporal dementia (FTD) with the Free and Cued Selective Reminding Test (FCSRT). Methods: The FCSRT was administered in 417 presymptomatic and symptomatic mutation carriers (181 chromosome 9 open reading frame 72 [ C9orf72 ], 163 progranulin [ GRN ], and 73 microtubule‐associated protein tau [ MAPT ]) and 290 controls. Group differences and correlations with other neuropsychological tests were examined. We performed voxel‐based morphometry to investigate the underlying neural substrates of the FCSRT. Results: All symptomatic mutation carrier groups and presymptomatic MAPT mutation carriers performed significantly worse on all FCSRT scores compared to controls. In the presymptomatic C9orf72 group, deficits were found on all scores except for the delayed total recall task, while no deficits were found in presymptomatic GRN mutation carriers. Performance on the FCSRT correlated with executive function, particularly in C9orf72 mutation carriers, but also with memory and naming tasks in the MAPT group. FCSRT performance also correlated with gray matter volumes of frontal, temporal, and subcortical regions in C9orf72 and GRN, but mainly temporal areas in MAPT mutation carriers. Discussion: The FCSRT detects presymptomatic deficits in C9orf72 ‐ and MAPT ‐associated FTD and provides important insight into the underlying cause of memory impairment in different forms of FTD.